Impact of nanostructured thin ZnO film in ultraviolet protection - Sasani Ghamsari, Morteza (Int J Nanomedicine, 2016)
Nanoscale ZnO is one of the best choices for ultraviolet (UV) protection, not only because of its antimicrobial properties but also due to its potential application for UV preservation. However, the behavior of nanostructured thin ZnO films and long-term effects of UV-radiation exposure have not been studied yet. In this study, we investigated the UV-protection ability of sol gel-derived thin ZnO films after different exposure times. Scanning electron microscopy, atomic force microscopy, and UV-visible optical spectroscopy were carried out to study the structure and optical properties of the ZnO films as a function of the UV-irradiation time. The results obtained showed that the prepared thin ZnO films were somewhat transparent under the visible wavelength region and protective against UV radiation. The UV-protection factor was 50+ for the prepared samples, indicating that they were excellent UV protectors. The deposited thin ZnO films demonstrated promising antibacterial potential and significant light absorbance in the UV range. The experimental results suggest that the synthesized samples have potential for applications in the health care field.